Pengetahuan Diri terhadap Kebersihan Tubuh pada Remaja - Lu’lu’ul Farodissa; Eppy Setiyowati; Novia Trisnasari Amini; Nurul Khasanah; Sailanur Rohmah; Yashinta Elma Gustiyani; Mochammad Agung Hamzah Wicaksono (CV. Ulil Albab Corp, 2023)
Knowledge of body hygiene is a critical issue as a determinant of adolescent health status. One of the efforts in maintaining and caring for the cleanliness of all members of the body is personal hygiene. The study aims to analyze the relationship between knowledge and body hygiene in adolescents at the Syaikhona Kholil 2 Islamic Boarding School Madura. Descriptive cross sectional manuscript research design. The sample is 42 people. Data collection using a questionnaire. The level of knowledge of adolescents at the Syaikhona Kholil 2 Islamic Boarding School Madura is categorized into 3, namely low, medium, and high. From the result of the study showed that as many as 12 respondents (28,56%) were in the low category, 20 respndents (47,62%) were in the medium category, 10 respondents (23,8%) were in the high category. Spearman test result with p-value 0,008<0,05 there is a significant relationship between knowledge and body hygiene in adolescents at the Syaikhona Kholil 2 Islamic Boarding School Madura will pay more attention to body hygiene and it is hoped that the boarding school supervisors will often monitor adolescents who are related to body hygiene.